Comparative analysis of the financial impact of the CSP in the Islamic, conventional and social banking model - De Zuhrah, Eliesa; Iglesia, Izzeldin (Inovasi Analisis Data, 2024)
Objective; This research explores the financial implications of Corporate Social Performance (CSP) based on Islamic, Conventional, and Social Banking models. Through the lens of this Study, which explores the relationship between CSP and financial performance, this paper highlights the heterogeneity evident amongst these banking models: in terms of the way they integrate CSP; and in terms of the financial benefits they gain from CSP initiatives.Methods; A regression between the Islamic, Conventional and Social Banking institutions using the Generalized method of moments (GMM). Methodology When it comes to the analysis, the methodology employed financial data retrieved from 120 banks, with a total number of 819 observations spanning over a certain time interval. The model risk assessment of CSP impact on financial performance based on ROAA, Size, CAR, and other financial valuesResults; CSP has a positive effect on financial performance in both the Islamic and Conventional Banking models with the existence of a significant relation for models like Return on Assets (ROAA) financial performance. Although the results for the influence of CSP on Islamic and Conventional bank models seem more pronounced, this impact appears less significant in Social Banking models. Whereas it has been observed that in some of the results CSP, with some banking-specific variables (IBSP, SBSP, and CBSP), plays a significant role in the improvement of their financial indicators; therefore, it is proved that CSP is a crucial strategy for them and contributes significantly to financial prosperity.Novelty; This study offers new comparative data on the financial consequences for CSP across differing banking models, substantiating how each adapts to and gains from these socially conscious undertakings. This provides insights that goes beyond general CSP analyses as it embeds the analysis in the particular contexts of Islamic, Conventional and Social Banking unlike prior studies.Research Implications; The findings imply that banking institutions, including both Islamic and Conventional banks, should give more attention to CSP initiatives to improve their financial performance. Lawmakers and financial regulators might promote an environment conducive to socially responsible banking. Future studies can investigate long-term impacts of CSP, including interactions with financial aspects across several industries.